ANALYSIS OF GROUND WATER QUALITY OF NAVNAGAPUR, DIST.AHMEDNAGAR (USING W.Q.I.) - Aishwarya V. Khare; Swapnil N. Ghule; Uday V. Kandake; Sagar S. Bhagwat; DR. A.J. Shirke (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Water is essential for all living organisms for their existence and metabolic process. Unethical human intervention in natural system and over exploitation of groundwater resources induces degradation of its quality. In many instances groundwater is used directly for drinking as well as for other purposes, hence the evaluation of groundwater quality is extremely important. The present study is aimed to analyze the underground water quality at Ahmednagar. In this study 30 water samples were collected from 15 places and analyzed for 7 water quality parameters for evening and morning. The study reveals that the area under study falls in moderately polluted category. The ground water of Ahmednagar city needs some treatment before consumption and it also needs to be protected from contamination